Metode bimbingan lembaga tabung haji terhadap jemaah haji Malaysia: satu penilaian awal - Hasanulddin, Mohd; Engku Ahmad Zaki, Engku Alwi; Jamalluddin, Hashim (Penerbit Universiti Sultan Zainal Abidin, 2020)
Lembaga Tabung Haji (TH) or Malaysian Hajj Fund Board is an institution that manages the savings of the Malaysian Muslims as well as the pilgrimage of Malaysian pilgrims from the homeland to the most relevant of all. One of the most important aspects is the teaching and guidance towards the pilgrims which considered as the heart of the holy journey. There is a perception that the approach to pilgrimage and umrah brought by TH is too narrow, rigid, harsh and unfriendly to the congregation. This perception invokes the credibility of TH's credibility in conducting Malaysian pilgrims. Therefore, this paper will highlight the TH guidance method for Malaysian pilgrims and make a brief assessment of it. The study used document analysis methods and interviews and then analyzed using content analysis and comparison methods. Studies show that TH has its own approach and manhunt in its guidance to Malaysian pilgrims. It is regulated by the highest body known as the TH-JAKIM Pilgrim Expert Committee Member (AJPIH). From the side of the jurisprudent resources methods, the references used is the authority that reflects the credibility of this TH guidance. The guidance provided is in line with the al-Shafi‘e scholar's approach, and the panel of authors also has a relatively flexible approach when discussing specific legal issues. This study can contribute to the resolution of the scientific and critical issues raised. In conclusion, the pilgrimage and umrah guidance to the target group should be emphasized and strengthened so that everyone can get the benefits from it.